A Model of Short-Term Capital Movements, the Foreign Exchange Market and Official Intervention in the UK, 1963-1970 - Hutton, John P. (Review of Economic Studies, 1977)
Journal Article A Model of Short-Term Capital Movements, the Foreign Exchange Market and Official Intervention in the UK, 1963–1970 Get access John P. Hutton John P. Hutton University of York Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 44, Issue 1, February 1977, Pages 31–41, https://doi.org/10.2307/2296971 Published: 01 February 1977 Article history Received: 01 August 1974 Accepted: 01 February 1976 Published: 01 February 1977